2017
DOI: 10.1017/s1368980017003251
|View full text |Cite
|
Sign up to set email alerts
|

Association between overweight/obesity and eating habits while watching television among primary-school children in the city of Shiraz, Iran

Abstract: TV viewing for ≥2 h daily increases the risk of being obese in Iranian children aged 6-10 years, independent of physical activity. Further, breakfast consumption while watching TV may increase the risk of overweight/obesity, independent of total TV viewing time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
2
13
0
8
Order By: Relevance
“…With regard to sedentary and nutritional habits and despite the fact that 74⋅4 % of the participants in our studies performed <3 h of physical activity per week, no statistically significant differences were found in the nutritional status of the patients. This is a finding that is consistent with the one reported by Smetanina et al in Lithuania ( 18 ) , but it is different from what was reported in Brazil ( 25 , 36 , 37 ) , Mexico ( 38 ) , Australia ( 39 ) , Egypt ( 40 ) , Nigeria ( 33 ) , Nepal ( 31 ) , Iran ( 41 ) and among others ( 23 , 42 ) . The relationship between the educational level of the parents and the nutritional status of the children continues to be contradictory, because some studies have reported higher frequencies of overweight or obesity in children whose parents have a higher educational level ( 25 , 31 , 35 , 43 ) , yet, other studies associate less education with higher rates of overweight/obesity ( 18 ) .…”
Section: Discussionsupporting
confidence: 83%
“…With regard to sedentary and nutritional habits and despite the fact that 74⋅4 % of the participants in our studies performed <3 h of physical activity per week, no statistically significant differences were found in the nutritional status of the patients. This is a finding that is consistent with the one reported by Smetanina et al in Lithuania ( 18 ) , but it is different from what was reported in Brazil ( 25 , 36 , 37 ) , Mexico ( 38 ) , Australia ( 39 ) , Egypt ( 40 ) , Nigeria ( 33 ) , Nepal ( 31 ) , Iran ( 41 ) and among others ( 23 , 42 ) . The relationship between the educational level of the parents and the nutritional status of the children continues to be contradictory, because some studies have reported higher frequencies of overweight or obesity in children whose parents have a higher educational level ( 25 , 31 , 35 , 43 ) , yet, other studies associate less education with higher rates of overweight/obesity ( 18 ) .…”
Section: Discussionsupporting
confidence: 83%
“…Research demonstrates that the use of online games is now growing rapidly (12). Watching time in childhood is associated with overweight/obesity, possibly due to dual sedentary problems and the connection between watching time and snacking (13,14). Whereas inactive lifestyles involve all children, it is likely to have the greatest influence on urban children who lack access to places where they can sustain social distancing.…”
mentioning
confidence: 99%
“…Avoiding television viewing while eating meals was associated with lower odds of obesity and overweight [23]. Besides, a few other studies also concluded that the children watching television while eating were prone to obesity/overweight [24,25]. Measures should be taken to reduce the food consumption during TV viewing as it may lead to unconsciousness intake of more calories and high-fat food.…”
Section: Discussionmentioning
confidence: 99%